Two phase uprighting of mesially impacted third molar, using skeletal anchorage - Valarelli, Fabrício; Pinto, Rayane Oliveira [UNESP]; Higa, Rodrigo Hitoshi; Pesantes, Carlos; Camacho Baur, Karlyn Maria R.; Grec, Roberto (Dental Press International, 2019)
Molars severely inclined in mesial position cause periodontal problems and disharmony in occlusion. Sometimes, its uprighting is indicated, even in an unfavorable position, to restore periodontal health and balance the occlusion without the need of prosthetic rehabilitation. The aim of this work is to describe the uprighting of a mesial-inclined lower third molar using skeletal anchorage, in the posterior region of the right side of the mandible. The patient was previously submitted to extraction of the first mandibular molar and presented generalized external apical resorptions. The maximum anchorage was performed in two different locations and in two stages. The first step consisted in the installation of an anchorage device in the mandibular ramus, in a distal position to the impacted tooth. The second stage consisted in mini-implant insertion in the intra-radicular space between the second molar and the second premolar in the same side, and the use of a TMA cantilever. The proper planning of the anchorage made possible to upright the tooth #48 under biomechanical control of the side effects, in a simple and easy way. At the end of the treatment, the harmony returned to the occlusion and the dentoalveolar structures were preserved.
Verticalização, em duas fases, de terceiro molar inferior impactado mesialmente, usando ancoragem esquelética
Keywords: Corrective; Orthodontic anchorage procedures; Orthodontics; Tooth movement techniques